MAGIS: mobile augmented-reality games for instructional support - Rodrigo, Ma. Mercedes T. (Archīum Ateneo, 2018)
We present Mobile Augmented-Reality Games for Instructional Support (MAGIS), a framework for the development of mobile augmented-reality (AR) games for education. The framework supports off-the-shelf, state-of-the-art technologies that enable AR tracking and rendering on consumer-level mobile devices, and integrates these technologies with content-generation tools that simplify the development of educational AR games, especially those that extensively use narrative-based game design and player-location tracking such as location-based historical or museum adventure games. We use Igpaw: Intramuros, a proof-of-concept game developed using MAGIS, to help describe the current state of the framework and to show its efficacy for implementing outdoor location-based educational games, and we briefly outline future development plans to improve MAGIS’ AR support (especially those involving indoor scenarios) as well as to improve the instructional design and authoring phases of AR applications written using this framework.